The role of dietary sodium intake on the modulation of T helper 17 cells and regulatory T cells in patients with rheumatoid arthritis and systemic lupus erythematosus. - Rossana Scrivo; Laura Massaro; Cristiana Barbati; Marta Vomero; Fulvia Ceccarelli; Francesca Romana Spinelli; Valeria Riccieri; Alessandra Spagnoli; Cristiano Alessandri; Giovambattista Desideri; Fabrizio Conti; Guido Valesini (PLoS ONE)
We aimed at investigating whether the frequency and function of T helper 17 (Th17) and regulatory T cells (Treg) are affected by a restriction of dietary sodium intake in patients with rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). We enrolled RA and SLE patients not receiving drugs known to increase urinary sodium excretion. Patients underwent a dietary regimen starting with a restricted daily sodium intake followed by a normal-sodium daily intake. The timepoints were identified at baseline (T0), after 3 weeks of low-sodium dietary regimen (T3), after 2 weeks of normal-sodium dietary regimen (T5). On these visits, we measured the 24-hour urinary sodium excretion, the frequency and function of Th17 and Treg cells in the peripheral blood, the serum levels of cytokines. Analysis of urinary sodium excretion confirmed adherence to the dietary regimen. In RA patients, a trend toward a reduction in the frequencies of Th17 cells over the low-sodium dietary regimen followed by an increase at T5 was observed, while Treg cells exhibited the opposite trend. SLE patients showed a progressive reduction in the percentage of Th17 cells that reached a significance at T5 compared to T0 (p = 0.01) and an increase in the percentage of Treg cells following the low-sodium dietary regimen at both T1 and T3 compared to T0 (p = 0.04 and p = 0.02, respectively). No significant apoptosis or proliferation modulation was found. In RA patients, we found a reduction at T5 compared to T0 in serum levels of both TGFβ (p = 0.0016) and IL-9 (p = 0.0007); serum IL-9 levels were also reduced in SLE patients at T5 with respect to T0 (p = 0.03). This is the first study investigating the effects of dietary sodium intake on adaptive immunity. Based on the results, we hypothesize that a restricted sodium dietary intake may dampen the inflammatory response in RA and SLE patients.